Hubungan Kecemasan dengan Kadar Nilai Glukosa Darah Pasien Diabetes Melitus di RSUD Fakfak - Apricilia Yuniarti Talla; Erna Melastuti; Indah Sri Wahyuningsih (PPNI UNIMMAN, 2025)
Diabetes mellitus is a chronic metabolic disease that affects not only the physical condition but also the psychological aspect of patients, particularly anxiety. This psychological condition can influence blood glucose stability and potentially worsen the clinical state of patients. The aim of this study was to analyze the relationship between anxiety and blood glucose levels among patients with diabetes mellitus at Fakfak General Hospital. The study applied a quantitative approach using an observational analytic method with a cross-sectional design. The sample consisted of 50 patients selected through total sampling. Anxiety data were collected using a questionnaire, while blood glucose levels were obtained from laboratory results. Data were analyzed using univariate and bivariate methods with the Chi-Square test at a significance level of p < 0.05. The findings showed that most patients experienced anxiety (96%) and the majority had normal blood glucose levels (70%). The Chi-Square test revealed a p-value of 0.000, indicating a significant relationship between anxiety and blood glucose levels in patients with diabetes mellitus at Fakfak General Hospital. This study highlights the importance of addressing psychological conditions as part of a comprehensive diabetes management program. It is recommended that health care services provide special attention to anxiety management as an effort to improve the quality of life of diabetic patients.